Colloidal Gradated Alloyed (Cu)ZnInS/ZnS Core/Shell Nanocrystals with Tunable Optical Properties for Live Cell Optical Imaging. Issue 21 (4th June 2018) - Selvaraj, Joicy; Mahesh, Arun; Baskaralingam, Vaseeharan; Dhayalan, Arunkumar; Paramasivam, Thangadurai
Abstract: In this work, Cd‐free, oleophilic (Cu)ZnInS(core)−ZnS(shell) core/shell quantum dots (QDs) with varying Cu content in the core and shell thickness were synthesized by heating‐up method (core) followed by hot‐injection route (shell). Effect of Cu ion doping (in core) and shell growth on the structural and optical properties of (Cu)ZnInS−ZnS core/shell QDs is reported. Incorporation of Cu ions causes the crystalline phase transformation of zinc blende ZnInS ternary alloy to wurtzite Cu−Zn−In−S quaternary alloy. The (Cu)ZnInS alloyed core QDs are encapsulated with a wider bandgap ZnS shell with gradient interface. The photoluminescence of (Cu)ZnInS core QDs exhibits wide tunable multicolor emissions from green (535 nm) to deep red (683 nm) with large Stokes shift. After the growth of ZnS layer, the PL peak position and absorption edge undergo a hypsochromic shift with enhanced photoluminescence quantum yield up to 47.31%, which is due to the partial cation exchange of Cu + and In 3+ with Zn 2+, yielding a graded core/shell structure with smooth potential interface. The radiative excited state lifetime is lengthened from 22.91 ns to 291.11 ns. The mercaptoundecanoic acid (MUA) functionalized QDs have been successfully used for in vitro fluorescence cellular imaging of HEK‐293 and HeLa cells. These QDs are cell permeable and suitable for visible light induced multicolor fluorescence‐based cellular imaging. Abstract : This work represents the effect of Cu ion doping (in the core quantum dots) on the structural and optical properties of (Cu)ZnInS−ZnS core/shell QDs synthesized by phosphine free heating‐up method followed by hot‐injection route. The core/shell quantum dots featured compositional dependent tunable optical properties, large Stokes shift, longer photoluminescence lifetime, higher photoluminescence quantum yield, good aqueous dispersibility, and biocompatibility. The mercaptoundecanoic acid functionalized QDs have been successfully used for in‐vitro fluorescence cellular imaging of HEK‐293 and HeLa cells.